Persepsi Mahasiswa terhadap Pemanfaatan Aplikasi Rstudio sebagai Media Bantu Pembelajaran Statistika - Mariyadi Mariyadi (Universitas Ivet, 2025)
This study aims to analyze student perceptions regarding the use of RStudio application to analyze ordinal data in statistics learning. The method used in this research is qualitative research. The data in this study are responses from students of the Informatics Engineering Study Program, Faculty of Engineering, Tanjungpura University in the 2022/2023 second semester. The data obtained were then analyzed using thematic data analysis techniques to obtain themes that can describe student perceptions of the use of the RStudio application to analyze ordinal data in statistics learning. This study succeeded in revealing the themes of perception, namely perceptions of Ease of Use, Application Sophistication, Application Usability, and Continuity of Use